Proses Penciptaan Dan Penyajian Karya Patung Publik Pada Jogja Street Sculpture Project #5 - Rahayu, Ananta Dewi; Rosidi, Muhammad Rain; Wicaksono, Satrio Hari (Journal of Contemporary Indonesian Art, 2024)
The Jogja Street Sculpture Project (JSSP) exhibition is a programme by the Indonesian Sculptors Association (API) in collaboration with the Culture Service in the form of a public sculpture. The fifth JSSP, with the theme Ruwat Gatra Rasa: Redefining Form and Space, is located along Jalan Malioboro. The author researches the creative process of creating and presenting public sculpture using a qualitative descriptive method with an approach to the theory of the creation process, the theory of the function of art, the presentation of public sculpture, and the elements of sculpture. Data collection was carried out through a literature review, interviews, and observations. Public interest is present in four stages of creation, (1) Pre-Design, (2) Design, (3) Realization, and (4) Presentation. Aspects of public response are also explained, where anticipation of public interaction is also taken into account in the process of creating works exhibited by artists and the organizing committee. In the presentation aspect, the author examines the elements of sculpture that are present, the public response, and improvements made by the artist. Pameran Jogja Street Sculpture Project (JSSP) merupakan program Asosiasi Pematung Indonesia (API) yang bekerjasama dengan Dinas Kebudayaan, berbentuk pameran patung di ruang publik. JSSP kelima dengan tema Ruwat Gatra Rasa: Redefining Form and Space berlokasi di sepanjang Jalan Malioboro. Penulis meneliti tentang proses kreasi penciptaan dan penyajian seni patung publik menggunakan metode deskriptif kualitatif dengan pendekatan teori proses kreasi, teori fungsi seni, penyajian patung publik, dan elemen-elemen seni patung. Pengumpulan data dilakukan dengan kajian pustaka, wawancara, dan observasi. Kepentingan publik hadir dalam empat tahapan penciptaan, (1) Pra Perancangan, (2) Perancangan, (3) Perwujudan, dan (4) Penyajian. Aspek respon publik juga dipaparkan, di mana antisipasi interaksi publik juga diperhatikan dalam proses penciptaan karya yang dipamerkan oleh seniman dan panitia penyelenggara. Dalam aspek penyajian, penulis mengkaji elemen seni patung yang hadir, respon publik, dan perbaikan yang dilakukan seniman.